INTERVAL ESTIMATION FOR TWO PARAMETERS EXPONENTIAL DISTRIBUTION UNDER MULTIPLE TYPE-II CENCORING ON SIMPLE CASE WITH BOOTSTRAP PERCENTILE - Akhmad Fauzy; Noor Akma Ibrahim; Isa Daud; Mohd. Rizam Abu Bakar (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2003)
In the article, two methods are proposed to give the interval estimation for twoparameters exponential distribution under multiple type-II cencoring on simple case. Balakrishnan(1990) use approximate maximum likehood estimator to construct interval estimation. All of thesemethod need an assumtion that sample is exounentially distributed. Method give shorter intervalthan the traditional method and this method does not need an assumtion that the sample isdistributed exponentially